MODEL MANAJEMEN SUMBER DAYA MANUSIA DALAM PENGELOLAAN LUMBUNG PANGAN SELAMA PANDEMI COVID-19 DI KABUPATEN MALANG - Cakti Indra Gunawan; Agnes Quartina Pudjiastuti; Yulita Yulita (Unitri Press, 2021)
This study aims to describe the human resource management model in managing food barns during the Covid-19 pandemic in Malang Regency. The research method uses a literature review study design or a comparison of various literatures including journals, books, and other sources. The data analyzed using a qualitative descriptive approach. The results of the study indicate that there is a human resource management model in the management of food barns based on information technology, by integrating 4 elements such as the government, the private sector, farmers, as well as local communities and customs. The integration and involvement of 4 elements with Information Technoogy is very important in realizing a good human resource management model in the management of barns at Covid-19 era in Malang Regency.